2005
DOI: 10.1583/05-1646.1
|View full text |Cite
|
Sign up to set email alerts
|

Infected Endoluminal Stent-Graft: Implications for Endotension, Late Endoleaks, and Prophylactic Antibiotics

Abstract: Stent-graft infection may be a cause of unexplained endotension. Special culture techniques may be required to identify the infecting organism. Prophylactic antibiotics against skin organisms should be considered for all implantations and arterial diagnostic and therapeutic procedures traversing a stent-graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…This is thought to be owing to compression of surrounding structures and the local inflammatory response to such complications. Bacterial colonisation of aortic thrombus (which is retained during endovascular stenting) has also been proposed as a source of graft infection 2. This patient had several risk factors including an emergent procedure and a postoperative endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be owing to compression of surrounding structures and the local inflammatory response to such complications. Bacterial colonisation of aortic thrombus (which is retained during endovascular stenting) has also been proposed as a source of graft infection 2. This patient had several risk factors including an emergent procedure and a postoperative endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…O paciente pode apresentar-se com febrícula e sintomas frustros em casos iniciais ou de pequena repercussão sistêmica; porém, também pode apresentar-se com abscesso localizado, pseudoaneurisma, fístula aortoentérica, bacteremia e sepse [20][21][22][23][24][25][26][27][28] . Alguns pacientes com endopróteses em aneurisma de aorta podem manifestar endotensão inexplicada, a qual pode associar-se à endoprótese infectada 29 . Ao se avaliarem apenas pacientes submetidos ao implante de endopróteses aorto-ilíacas, observam-se abscessos retroperitoniais em 29%; fístula inguinal em 14,5%; embolia sép-tica em 11,3% e choque hemorrágico em 9,6% dos casos infectados 14 .…”
Section: Aspectos Clínicosunclassified
“…Alguns autores advogam o uso de profilaxia antimicrobiana nos procedimentos percutâneos subsequentes ao implante de endoprótese e que poderiam contaminá-la, especialmente nas primeiras semanas, quando a proteção neointimal ainda não se desenvolveu por completo 29 .…”
Section: Profilaxiaunclassified
“…Another rare cause could be aortic stent infection, an uncommon but life-threatening complication that was first published in 1999. [58][59][60] Researchers have suggested that the diagnosis of stent-graft infection should be considered in all cases of unexplained endotension. 59 Hygroscopic fluid accumulation may be possible, and much is yet to be understood about the behavior of the thrombus in the excluded aneurysm sac.…”
Section: Endotension and Endoleakmentioning
confidence: 99%